Solar Power Plant Planning in Supporting Sustainable Energy Transition in Remote Islands: Enggano Island Case Study - Sri Nugroho, Wisnu; Sambegoro, Poetro Lebdo (ITB Graduate School Conference, 2025)
Enggano Island is the outermost island of Indonesia that has challenges in providing sustainable electricity. There are 3 scenarios planned to support the sustainable energy transition, namely the configuration scenario (a) hybrid diesel with PV, scenario (b) hybrid diesel with PV and battery, and scenario (c) PV and battery. Based on the optimization results, scenario (b) is the most optimal configuration, consisting of 1,097 kWp PV, 700 kW diesel, and 32 battery units. The system can produce electricity up to 1.92 GWh/year. Diesel functions as an energy reserve if PV and batteries are unable to meet the load needs. The total NPC system reaches IDR 59.82 billion and the cheapest LCOE value for other scenarios is IDR 3,357.59/kWh. In terms of the environment, this configuration has an RF value of 75.8% with CO₂ emissions of 339,181 kg/year, which is very small when compared to the diesel system on Enggano Island.